PENGARUH SEMINAR PRA-KERJA DALAM PENGEMBANGAN SELF CONCEPT (STUDI KASUS PADA KARANG TARUNA DI DESA MUKTIWARI, CIBITUNG) - RENI NOVIA (Interpretasi: Communication & Public Relations, 2022)
This research is based on available data, the number of graduates who are able to work has not been fulfilled, due to the lack of self-concept ability. The formulation of the problem is how much influence pre-employment seminars have in developing self-concept (a case study on youth groups in Muktiwari village, Cibitung)?, with the aim of the study being to find out how much influence pre-employment seminars have in developing self-concept (case studies on coral reefs). cadets in Muktiwari Village, Cibitung). The research method used was a quantitative correlation, with a population of 30, data collection through questionnaires with sampling technique, simple random sampling, with a total sample of 16 people. The result of this research is that there is a significant effect between pre-employment seminars and self-concept development. It is recommended for researchers who have an interest in similar research, by increasing the number of respondents and the coverage area, thus enriching the data in the study. And the results of the data found that the dimensions of self-concept development factors are not all self-concepts developed from educational backgrounds, but interactions from families, especially parents, have a significant influence on self-concept development.